(untitled) (Research, Society and Development, 2022)
This article aims to identify the contributions that Creative Learning can provide to students with blindness or low vision both from the point of view of inclusion and in the process of skills development. It also stands out when mentioning the importance of this methodology as a pedagogical tool. To carry out this work, scientific articles and reports available on governmental and specialized websites were analyzed. In the final considerations, the importance of using Creative Learning for the inclusion of students with severe visual impairment in the school environment and their contributions in the teaching-learning process is highlighted.